The psychological mechanism of Self-objectification: the interaction between sociocultural pressures and the self-system - Liu, Zhennan; Fu, Mei; Shi, Jianmei; Hu, Yinying; Gao, Xiangping (Frontiers in Psychology, 2025)
Self-objectification involves adopting an observer’s perspective on the body and prioritizing appearance over internal attributes, which is most common in women. We propose that self-objectification arises from the interplay between sociocultural pressures and the self-system rather than from sociocultural forces alone. In this account, self-concept clarity functions as a susceptibility factor that conditions the internalization of appearance norms; internalization and upward social comparison then increase body surveillance and appearance-focused negative affect (e.g., body shame, dissatisfaction). Over time, these experiences consolidate negative self-schemas and ruminative thinking, which help sustain and amplify self-objectification. Consequently, self-objectification is associated with reduced interoceptive awareness and compromised self-regulation, with downstream implications for cognition, mood, and health-related behaviors. We outline priorities for future research: (a) testing the moderating role of self-concept clarity across development, (b) clarifying how negative self-schemas and rumination maintain self-objectification over time, (c) distinguishing state versus trait/chronic forms and their effects on regulation, and (d) integrating mechanistic assays with intervention studies (e.g., mindfulness, self-compassion, cognitive reappraisal). Taken together, this framework highlights the intertwined influences of sociocultural environments and self-structure in the emergence and persistence of self-objectification.